The Role of Education in the Implementation of Shared Decision Making in Emergency Medicine: A Research Agenda. (25th November 2016) - Chen, Esther H.; Kanzaria, Hemal K.; Itakura, Kaoru; Booker‐Vaughns, Juanita; Yadav, Kabir; Kane, Bryan G.
Abstract: Shared decision making (SDM) is a patient‐centered communication skill that is essential for all physicians to provide quality care. Like any competency or procedural skill, it can and should be introduced to medical students during their clerkships (undergraduate medical education), taught and assessed during residency training (graduate medical education), and have documentation of maintenance throughout an emergency physician's career (denoted as continuing medical education). A subgroup representing academic emergency medicine (EM) faculty, residents, content experts, and patients convened at the 2016 Academic Emergency Medicine Consensus Conference on SDM to develop a research agenda toward improving implementation of SDM through sustainable education efforts. After developing a list of potential priorities, the subgroup presented the priorities in turn to the consensus group, to the EM program directors (CORD‐EM), and finally at the conference itself. The two highest‐priority questions were related to determining or developing EM‐applicable available tools and on‐shift interventions for SDM and working to determine the proportion of the broader SDM curriculum that should be taught and assessed at each level of training. Educating patients and the community about SDM was also raised as an important concept for consideration. The remaining research priorities were divided into high‐, moderate‐, and lower‐priority groups. Moreover, there was consensus that the overall approach to SDM should be consistent with the high‐quality educational design utilized for other pertinent topics in EM.